Sewage disposal works a guide to the construction of works for the prevention of the pollution by sewage of rivers and estuaries - Crimp, W. Santo (Charles Griffin, 1894)
This illustrated guide to the construction of sewage works brings together some of the best examples of recent works.
Includes index.
Keywords: Sewage disposal plants -- Design and construction.; elektronické knihy; electronic books